Alocação intertemporal e múltiplos usuários: estudo de caso sistema Jaguaribe - metropolitano - Cid, Daniel Antônio Camelo (2017)
The uncertainties regarding the availability of water in the Brazilian semi-arid region mark the difficulties of the management of water resources in this region. In order to combat these uncertainties, reservoirs are used as water regulators during periods of drought. The operation of these reservoirs and the allocation of available water are a decision-making process, whose choices can be aided by simulation models and optimization of the water resources system. This paper proposes the definition of a reservoir operation rule with a view to promoting the equitable and efficient allocation of water resources, integrating the short and long term allocation mechanisms. The application site was the Jaguaribe-Metropolitano reservoir system, located in the state of Ceará. The methodology incorporated the preference of the water managers in the definition of risks of thinning, rationing of uses and water transfer between the basins, which served as criteria for the definition of the policy of operation of the reservoirs with safeguards. The generated operating rule proved to be successful, capable of being applied to the actual operation of the system. The reservoirs that were previously subject to collapse due to the installed demand being higher than the regularized flow, obtained a good performance in the simulations.